Kotlin assimilating the Android ecosystem: An appraisal of diffusion and impact on maintainability - Coppola, Riccardo; Fulcini, Tommaso; Ardito, Luca; Torchiano, Marco (The Journal of systems and software, 2025)
Kotlin was introduced in 2011 as an alternative to the Java programming language, promising to address many of its predecessor’s limitations and positioning itself as a better option for application maintainability. In 2017, Kotlin became a first-class language for Android application development, complete with extensive tool support. This paper aims to empirically assess the diffusion of Kotlin in developing Android applications and to investigate the impact of Kotlin adoption on application maintainability. We mined 2708 open-source Android applications from F-Droid, focusing on the extent of Kotlin code presence, their popularity, and maintainability. This analysis adopted a set of six code metrics proxies. The proportion of applications developed with Kotlin, either in conjunction with Java or exclusively, has continuously increased over the past five years. Currently, Kotlin is used in approximately 40% of the projects. The adoption of Kotlin in application development appears to be linked to greater popularity among end-users and developers when compared to the applications written in Java. Notably, the exclusive use of Kotlin in projects significantly enhances all the considered code maintainability metrics. We conclude that Kotlin is rapidly gaining ground in the Android ecosystem. This trend is likely due to Kotlin’s fulfilment of its promise as a superior alternative to Java, particularly in terms of maintainability.